Peran Media Sosial Terhadap Jual Beli Online Skincare Ditinjau Dari Hukum Islam Di Toko Ms Glow Nganjuk - Agus Thohawi; Subekan Subekan; Titi Nur Fatimah (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2021)
This study aims to obtain clarity on the role of social media in online sales in terms of Islamic law. Thus, social media must be able to provide a clear and directed picture. The focus of this research is What is the role of social media in buying and selling Ms Glow's skincare online? How do social media factors influence the buying and selling of MS Glow skincare online in Nganjuk district? And also How is the Islamic law review of buying and selling MS Glow skincare online on social media? The method in this research uses a qualitative approach by collecting data through observation, interviews and documentation. The data analysis technique is through data reduction, data unitization and categorization, data display (data display), and conclusion drawing. The results in this study are the role of social media in buying and selling online at Ms. Glow Nganjuk's shop is buying and selling using the social media system or with resellers / dropshipping. This online buying and selling transaction can be carried out using a contract, namely ba'i as-Salam. Social media factors can increase product sales, minimize costs used for promotion, interact with consumers and expand market networks. A review of Islamic law on buying and selling of Ms Glow's skincare online on social media at Ms Glow Nganjuk's shop has fulfilled the principles and conditions of buying and selling in Islamic law.